«Rend your heart and not your garments»: A comment on Joel’s First book, chapter 2, verse 13 - Aguirre Martínez, Guillermo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper shows an interpretation of the following phrase taken from Joel’s First book, 2, 13: «Rend your heart and not your garments». From the prophet’s exhortation to replace the Ancient Law by a recent one, we will discuss about the question of the «I» and the «you», this is, about the intersubjective relations as a way of opening towards a wider reality.
Keywords: Joel; Old Testament; New Testament; pain; love